Characterization of Transgenic Mice that Secrete Functional Human Protein C Inhibitor into the Circulation - Wagenaar, Gerry T. M.; van Vuuren, A. J. Hanneke; Girma, Merone; Tiekstra, Margriet J.; Kwast, Liane; Koster, Johanna G.; Rijneveld, Anita W.; Elisen, Marc G.L.M.; van der Poll, Tom; Meijers, Joost C.M. (Thrombosis and Haemostasis, 2000)
Protein C inhibitor (PCI) is a heparin binding serine protease inhibitor in plasma, which exerts procoagulant activity by inhibiting thrombomodulinbound thrombin or activated protein C (APC). Since the role of PCI in vivo is largely unknown we generated genetically modified mice with expression of human PCI mRNA in hepatocytes only. Three transgenic lines have been characterized. Transgenic mice did not show gross developmental abnormalities. Two lines showed a pericentral and one line showed a periportal expression pattern of human PCI mRNA in the liver. Genetically modified mice secreted a functional transgenic protein into the circulation (3-5 µg/ml plasma in heterozygous mice and 10 µg/ml in homozygous mice), which inhibited human APC activity in the presence of heparin. Interestingly, transgenic mice in which human PCI was expressed periportally in the liver had the highest specific activity. Endogenous mouse PCI mRNA could only be detected in the male and female reproductive system, but not in the liver, indicating that endogenous PCI levels in the circulation are low or even absent in mice. These results demonstrate that the human PCI transgenic mice are a suitable model for studying the in vivo role of PCI in blood coagulation.
Keywords: Serine protease inhibitor; hepatocyte; endotoxin; lipopolysaccharide; blood coagulation; zonation